Healing power of Malaysian seaweeds - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2011)
Seaweeds are macroalgae, that do not possess true roots, stems or leaves. However, some of the larger species possess attachment organs or holdfasts that have the appearance of roots, and there may also be a stem-like portion called a stipe, which flattens out into broad leaf-like portion or lamina.Seaweeds are classified into three divisions, Rhodophyta (red algae), Chlorophyta (green algae) and Phaeophyta (brown algae). The red algae are characterized by having red pigments called phycobilins, which mask the color of chlorophyll though some may show different colors. The group is essentially marine; only a few of the approximately 4,000 species live in fresh water. The green algae are largely unicellular and non-marine. They are typically bright green since chlorophyll is not masked by other pigments. The colors of brown algae vary from olive green to dark brown, due to a preponderance of yellow pigments, particularly fucoxanthin, over chlorophyll. Human consumption of brown seaweed (66.5%), red seaweed (33%) and green seaweed (5%) is high in Asian countries, mainly Japan, China and Korea. Seaweeds have been used since ancient times as food, fodder, fertiliser and medicinal drugs. Tropical seaweed, rich in dietary fibres and bioactive phenolic compounds, for example Eucheuma cottonii and Sargassum polycystum are used in food and medicine due to its anti-diabetic, anti-hypertensive, cardiovascular protective and anti-oxidative tissue protective properties.